1988
DOI: 10.1164/ajrccm/138.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cells Recovered by Bronchoalveolar Lavage: Comparison of Cytocentrifuge Preparations with the Filter Method

Abstract: Controversy exists as to the appropriate methods to use in the processing of bronchoalveolar lavage (BAL) fluid for total cell numbers and cellular differential analysis. It has been shown that cell losses (primarily lymphocytes) occur by the most commonly employed methods. Therefore, we examined the total cell and differential counts obtained by several methods of cytocentrifuge preparation and by the filter preparation in 46 consecutive patients with interstitial lung disease and 29 healthy volunteers underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 3 publications
1
25
1
Order By: Relevance
“…The number of cells (approximately 100 ϫ 10 6 to 150 ϫ 10 6 ), the cell type (approximately 80 to 90% monocytes/macrophages), and the volume of ELF (approximately 1 ml) are similar to the values that we and others have reported previously (1,2,4,7,10,26,29,33). Used with sensitive and specific drug assay techniques, this procedure permits an accurate estimation of the intrapulmonary drug concentrations in these compartments.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The number of cells (approximately 100 ϫ 10 6 to 150 ϫ 10 6 ), the cell type (approximately 80 to 90% monocytes/macrophages), and the volume of ELF (approximately 1 ml) are similar to the values that we and others have reported previously (1,2,4,7,10,26,29,33). Used with sensitive and specific drug assay techniques, this procedure permits an accurate estimation of the intrapulmonary drug concentrations in these compartments.…”
Section: Discussionsupporting
confidence: 80%
“…The number of cells from which drug was extracted was calculated by multiplying the number of cells per milliliter in BAL fluid times the volume (in milliliters) of BAL fluid that was centrifuged to produce the pellet. It has been noted, however, that centrifugation causes an average loss of 21% of the cells (33), so that the actual number of cells recovered postcentrifugation may be less than the number counted, and the actual antibiotic concentration may be proportionately more than we report here. The volume of ACs in the pellet suspension was calculated by using a mean macrophage cell volume of 2.42 l/10 6 cells (2).…”
Section: Methodscontrasting
confidence: 60%
“…The number of cells in 1.0 ml of pellet suspension was calculated to be equal to the number of cells in 1.0 ml of BAL fluid times 30. Because of cell loss during centrifugation, the actual number of cells recovered may be lower than the number counted and the antibiotic concentration may be approximately 20% higher than what we calculated (26). Differential cell counting was performed after spinning the specimen in a cytocentrifuge.…”
Section: Methodsmentioning
confidence: 94%
“…Other studies have not found that cytocentrifugation is responsible for loss of lymphocytes. In one study, it was found that differences in lymphocyte counts were due to the addition of serum to BALF [11]. In a second study, differences in lymphocyte counts were felt to be due to differences in methods used to fix and stain the cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Careful investigations have demonstrated that the method of processing of BALF can significantly affect data interpretation [7][8][9][10][11][12]. For example, the two most widely utilized methods, cytocentrifugation and membrane filtration, underestimate the content of lymphocytes and neutrophils, respectively [7,9,10].…”
Section: Technical Notementioning
confidence: 99%